Songs for Teaching Vocabulary: English Learning Media for Preschoolers - Aria Septi Anggaira; Nurul Aryanti; Suryadi Suryadi; Tusriyanto Tusriyanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
In terms of language acquisition, preschoolers are associated with the golden age. This led to the awareness of the importance of mastering English as early as possible. Vocabulary learning is an important aspect of learning a language because the basis of language is vocabulary. However, a lack of strategy in introducing English vocabulary is the problem faced by preschool teachers. This study is a literature review that aims to review the use of songs in vocabulary learning for preschoolers. In addition, the success of using songs in English vocabulary learning for preschoolers, which was reported by a lot of studies, is thought to be paramount to discuss. This study refers to 49 references which are books or articles from journals related to the use of songs as a medium in vocabulary learning for early childhood. Therefore, this article is intended to review the use of songs in English vocabulary learning for preschoolers. The English vocabulary, English children's songs, and development of English Vocabulary in preschoolers were presented descriptively. The review concludes that songs can be an alternative media in vocabulary learning for preschoolers.